The Baltic in the Bronze Age Regional Patterns, Interactions and Boundaries. - Hofmann, Daniela (Sidestone Press, 2022)
The Bronze Age is a time of increasing interaction with large-scale connections that cover vast parts of Europe. Some parts and regions of the Bronze Age are very well explored and for some very strong narratives of hierarchisation and differentiation, dependence on external raw material supplies and specialisation have been proposed. In other regions, however, only some of these aspects appear, even though networks of contact would at least have been possible.